Pedagogical Opportunities of Wrestling Sports in the Formation of a Sense of National Pride in Students (Eurasian Scientific Herald, 2022)
The article explores the use of physical education classes and extracurricular activities in wrestling to form a sense of national pride in students. Wrestling is also considered as one of the key factors in educating a harmoniously developed generation